2016
DOI: 10.1186/s13071-016-1670-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fluralaner administered either orally or topically for the treatment of naturally acquired Sarcoptes scabiei var. canis infestation in dogs

Abstract: BackgroundThe efficacy of fluralaner, formulated as a chewable tablet (Bravecto™) or topical solution (Bravecto™ Spot-on Solution), was evaluated against naturally acquired Sarcoptes scabiei var. canis infestation in dogs.MethodsThe study was performed in privately-owned dogs naturally infested with S. scabiei var. canis. All dogs living in the same household as the infested dog were enrolled into one of 3 groups (2 fluralaner treated and 1 negative control). All dogs within one household were administered the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 17 publications
5
22
0
Order By: Relevance
“…With a new mode of action and predominantly systemic activity, the isoxazoline ectoparasiticides have seen growing use in companion animals for the treatment of flea and tick infestations, and have been tested for a wide variety of blood-feeding arthropods [ 33 ], skin-dwelling mammal mites such as Sarcoptes scabei [ 17 , 20 ] and a few non- blood-feeders such as blow fly or mosquito larvae [ 15 ]. The latter study showed the lower threshold for significantly increased mortality for most target arthropods occurred at somewhere around 1 ppm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a new mode of action and predominantly systemic activity, the isoxazoline ectoparasiticides have seen growing use in companion animals for the treatment of flea and tick infestations, and have been tested for a wide variety of blood-feeding arthropods [ 33 ], skin-dwelling mammal mites such as Sarcoptes scabei [ 17 , 20 ] and a few non- blood-feeders such as blow fly or mosquito larvae [ 15 ]. The latter study showed the lower threshold for significantly increased mortality for most target arthropods occurred at somewhere around 1 ppm.…”
Section: Discussionmentioning
confidence: 99%
“…This mitigates cross-resistance to other chemotypes, and differing target sites between arthropods and mammals result in selective toxicity and mechanistically based safety [ 16 ]. Isoxazolines, including fluralaner, afoxalaner and sarolaner, are under development and are of increasing importance in the control of external parasites in dogs and cats, including mites [ 17 20 ]. The present study was conducted to determine if fluralaner possesses contact activity against O. sylviarum , and compare this activity with that of other acaricides commonly used against mite infestations of poultry.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of a single dose of fluralaner is an effective treatment for naturally acquired S. scabiei var. canis infestation in dogs [83], and recent data show that a single dose of oral fluralaner is as effective as a single dose of oral ivermectin for the treatment of human scabies, with cure rates of 86 and 83% 4 weeks after treatment, respectively [Goldust, unpubl. ; 84].…”
Section: Treatmentmentioning
confidence: 99%
“…Recent advances in longer lasting treatments for control of S. scabiei and other ecto-parasites (e.g. fluralaner, a newly developed, long-lasting, ecto-parasiticide) may be candidates for wombats(Taenzler, Liebenberg, Roepke, Frénais, & Heckeroth, 2016). Thus, an improved pharmaceutical agent in conjunction with other management changes (i.e.…”
mentioning
confidence: 99%